2015
DOI: 10.1042/bj20150518
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation outer proteins: double-edged swords of symbiotic rhizobia

Abstract: Rhizobia are nitrogen-fixing bacteria that establish a nodule symbiosis with legumes. Nodule formation depends on signals and surface determinants produced by both symbiotic partners. Among them, rhizobial Nops (nodulation outer proteins) play a crucial symbiotic role in many strain-host combinations. Nops are defined as proteins secreted via a rhizobial T3SS (type III secretion system). Functional T3SSs have been characterized in many rhizobial strains. Nops have been identified using various genetic, biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 107 publications
(229 reference statements)
0
115
0
Order By: Relevance
“…In Sinorhizobium fredii, mutations in genes coding for components of the T3SS machinery, including the extracellular appendages, completely block the secretion of Nops. However, inactivation of genes coding for potential effectors does not alter the secretion of other nodulation outer proteins (21). It is worth noting that the bands corresponding to the Nops previously identified in HH103, with the exception of NopD, which is not easy to detect in gels due to its high molecular mass, were present in the lanes corresponding to the parental strain HH103 Rif r and the nopI mutant (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In Sinorhizobium fredii, mutations in genes coding for components of the T3SS machinery, including the extracellular appendages, completely block the secretion of Nops. However, inactivation of genes coding for potential effectors does not alter the secretion of other nodulation outer proteins (21). It is worth noting that the bands corresponding to the Nops previously identified in HH103, with the exception of NopD, which is not easy to detect in gels due to its high molecular mass, were present in the lanes corresponding to the parental strain HH103 Rif r and the nopI mutant (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…All of these results indicated that NopI can be considered a nodulation outer protein. In Sinorhizobium fredii, mutations in genes coding for components of the T3SS machinery, including the extracellular appendages, completely block the secretion of Nops (21). The mutation of nopI and nopL did not affect secretion to the extracellular medium of Nops other than NopI and NopL, respectively, suggesting that they were not essential components of the T3SS machinery (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Type III secretion system (T3SS) [55] can either promote or impair the establishment of symbiosis, depending on the legume host [56], and has been characterized as a host determinant for rj1, Rfg1, Rj2 and Rj4 soybean cultivars [33, 57, 58]. The dominant soybean genes Rj2 and Rj4 restrict nodulation with specific strains of Bradyrhizobium [33].…”
Section: Insights From the Genome Sequencementioning
confidence: 99%